Nitrogen-doped graphene-supported zinc sulfide nanorods as efficient Pt-free for visible-light photocatalytic hydrogen production - Azarang, Majid; Sookhakian, Mehran; Aliahmad, Mousa; Dorraj, Masoumeh; Basirun, Wan Jefrey; Goh, Boon Tong; Alias, Yatimah (Elsevier, 2018)
Nitrogen-doped graphene-ZnS composite (NG-ZnS) was synthesized by thermal treatment of graphene-ZnS composite (G-ZnS) in NH3 medium. In the second step, the as-synthesized samples were deposited on indium tin oxide glass (ITO) by electrophoretic deposition for photocatalytic hydrogen evolution reaction. The as-prepared NG-ZnS-modified ITO electrode displayed excellent photocatalytic activity, rapid transient photocurrent response, superior stability and high recyclability compared to the pure ZnS and G-ZnS-modified ITO electrode due to the synergy between the photocatalytic activity of ZnS nanorods and the large surface area and high conductivity of N-graphene.